Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/1750-3841.15482
|View full text |Cite
|
Sign up to set email alerts
|

Coniferaldehyde ameliorates the lipid and glucose metabolism in palmitic acid‐induced HepG2 cells via the LKB1/AMPK signaling pathway

Abstract: Impaired lipid and glucose metabolism in the liver is a crucial characteristic of nonalcoholic fatty liver disease (NAFLD). Coniferaldehyde (CA), a kind of phenolic compound found in many edible plants, has multiple biological and pharmacological functions. However, since the effect and molecular mechanism of CA on hepatic lipid and glucose metabolism disorders in NAFLD remain unknown, this study investigated its impact on the lipid and glucose metabolism of palmitic acid (PA)‐induced HepG2 cells. Compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 58 publications
(93 reference statements)
1
18
0
Order By: Relevance
“…3 As recently reported, 200 μM PA markedly increased TG and TC contents by 70.07 and 75.21% in HepG2 cells, respectively. 16 This study created a high-fat model of AML-12 with 400 μM PA (for 24 h), which significantly induced lipid deposition, as indicated by increases in TG and TC contents. A previous study reported that GLA could reduce concentrations of TG, TC, and β-lipoprotein in mouse plasma, with efficiencies of up to 81.5, 68.2, and 64.8%, respectively.…”
Section: ■ Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…3 As recently reported, 200 μM PA markedly increased TG and TC contents by 70.07 and 75.21% in HepG2 cells, respectively. 16 This study created a high-fat model of AML-12 with 400 μM PA (for 24 h), which significantly induced lipid deposition, as indicated by increases in TG and TC contents. A previous study reported that GLA could reduce concentrations of TG, TC, and β-lipoprotein in mouse plasma, with efficiencies of up to 81.5, 68.2, and 64.8%, respectively.…”
Section: ■ Discussionmentioning
confidence: 70%
“…13,47 LKB1 is an upstream kinase, which can regulate autophagy by phosphorylating AMPK. In hepatocytes, PA treatment markedly decreased pLKB1/LKB1 and p-AMPK/AMPK protein expressions, 16 while PUFAs can increase LKB1 protein expression and promote AMPKα phosphorylation. 48 n-6 PUFAs increased AMPK activity and activated autophagy through TOR-independent signaling pathways.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 94%
“…9 Moreover, CA was reported to ameliorate glucose and lipid metabolism in HepG2 by LKB1/AMPK. 10 In addition, CA was also reported to prevent destruction of articular cartilage in a murine model by Nrf2/HO-1. 11 Another novel discovery of this study was that JAK2 and STAT1 proteins were the targets of CA.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is an important regulator of hepatic lipid metabolism, which can enhance insulin sensitivity and fatty acid oxidation. 33 Our results showed that AST administration could significantly enhance the expression of pAMPK in the liver of ageing mice (Figure 3 ), indicating that AST can activate AMPK in the liver. ACC1 is the downstream target of AMPK and can catalyse the production of malonyl‐CoA.…”
Section: Discussionmentioning
confidence: 62%
“…AST administration can significantly reduce the ratio of liver weight to body weight and reduce hepatic TG content (Figure 1), indicating that the liver plays an important role in AST‐mediated regulation of lipid metabolism. AMPK is an important regulator of hepatic lipid metabolism, which can enhance insulin sensitivity and fatty acid oxidation 33 . Our results showed that AST administration could significantly enhance the expression of pAMPK in the liver of ageing mice (Figure 3), indicating that AST can activate AMPK in the liver.…”
Section: Discussionmentioning
confidence: 69%